Impact of Store Environment on Impulse Buying Behavior - Mohan, G.; Sivakumaran, B.; Sharma, Piyush (Emerald Group Publishing Limited, 2013)
Purpose – This paper aims to explore the process by which four store environment (music, light, employee, and layout) and two individual characteristics (shopping enjoyment tendency (SET) and impulse buying tendency (IBT)) influence impulse buying behavior through positive and negative affect, and urge to buy impulsively. Design/methodology/approach – The data were obtained using a structured questionnaire from733 respondents in a mall survey conducted in Chennai, South India. Findings – In the structural model tested with AMOS, the authors found that store environment drove impulse buying (IB) through positive affect and urge. Results also showed that the personality variables (SET and IBT) influenced IB through positive affect and urge. This paper did not find support for the relationship between negative affect and urge. Research limitations/implications – Theoretically, the authors add to the list of antecedents of impulse buying, and to the outcomes of store environment. From a managerial viewpoint, the authors suggest that retail managers invest in improving the store environment to increase the level of impulse buying in their stores. Specifically, they need to focus on enhancing friendliness of store employees, playing appropriate music, designing proper layouts and having well-lit stores to encourage impulse buying. Originality/value – Prior research studied the elements of the store independently and also its long-term impact. To the best of the authors’ knowledge, their research is the first to study the impact of store environment (in conjunction with trait variables) on impulse buying.